Design and Implementation of a Web-Based Relay Maintenance Information System at the Substation - Sartika , Nike; Anugrah Firdaus, Aldi; Mardiati, Rina (P3M Politeknik Negeri Cilacap, 2025)
Protection relays detect disturbances or abnormal conditions in the electric power system, isolate disturbances, eliminate abnormal conditions, and produce signals or indications. One of the protection relays used in substations is the Over-Current Relay (OCR) and Ground Fault Relay (GFR). Routine maintenance of OCR and GFR is usually done by resetting or replacing the relay. However, the maintenance process was carried out manually using special test equipment, with the results recorded manually in a form, which was then digitized. This procedure is considered less effective. This study develops a web-based relay maintenance application using the waterfall method. This method was chosen because of its structured approach, complete documentation, and cost and processing time stability. The test results show that the web-based system functions according to the expected functionality. This application has been proven to facilitate and increase officers' effectiveness in relay maintenance based on a user survey. This application's OCR and GFR setting results are simulated using the ETAP 19.01 application for a short circuit fault scenario. The simulation results show that the relay works according to the inverse standard characteristics. The relay trip time for a fault on the 150kV side of the transformer is 2.2 seconds, while for a fault on the 20kV side, it is 7 seconds on Circuit Breaker 2 and 26 seconds on Circuit Breaker 1.